Need of Ontology Based Systems in HealthCare System - Andarmoyo, Sulistyo; Syandri, Gusmaizal; Thanh Nguyen, Phong; Laxmi Lydia, E.; Shankar, K. (Opción, 2019)
Recently on the Semantic Web the healthcare is consider as one of the finest topic. To match the concept to the indexed documents into s set of representative the textual query is transformed. For apt documents manually the end user still has to search. In this way it becomes a cru- cial task to detect the information of patients. The theory of object is its relationship is considered as Ontology. In information science and computer science the ontology encompasses a definition, representation and formal naming of the relations, categories and properties between entities, concepts and data that substantiate all, many or one domains of discourse.